FRI0579 RHEUMATOID FACTOR IS ASSOCIATED WITH FALSELY ELEVATED RESULTS IN COMMERCIAL IMMUNOASSAYS: DATA FROM AN EARLY ARTHRITIS COHORT. (2nd June 2020) - Gehin, J. E.; Klaasen, R. A.; Norli, E. S.; Syversen, S. W.; Goll, G. L.; Warren, D. J.; Kvien, T. K.; Nustad, K. J.; Mjaavatten, M. D.; Bolstad, N.
Abstract : Background: Immunoassays are used to measure a range of analytes in clinical laboratories. Rheumatoid factor (RF) and other patient antibodies, such as heterophilic antibodies, can bind animal antibodies used in immunoassays and cause erroneous results, which may lead to misdiagnosis and incorrect treatment of patients. 1 Objectives: To assess RF reactivity to animal antibodies and to test if selected commercial immunoassays are vulnerable to interference from RF-positive sera. Methods: Samples from 124 patients with RF-positive rheumatoid arthritis (RA) included in the Norwegian Very Early Arthritis Clinic (NOR-VEAC)-cohort 2 were included in the study. Samples from patients with seronegative RA (n=51) and psoriatic arthritis (n=15) from the same cohort were included as controls. Reactivity to mouse IgG1, mouse IgG2a, rabbit IgG, bovine IgG, sheep/goat IgG and human IgG was analysed using in-house interference assays detecting antibodies able to cross-link the animal or human antibodies. RF-positive sera with strong reactivity to mouse IgG1 were selected for testing in three commercial immunoassays previously shown to be susceptible to interference from heterophilic antibodies; Abbott Architect Total β-hCG assay, BioRad 27-plex cytokine assays and Roche Elecsys Soluble Transferrin Receptor (sTfR). 3 Samples were tested before and after addition of blocking aggregated murine IgG1 (interference protection). Interference was defined as a discrepancy between the unblocked and blocked samples likely to influence clinical interpretation of the results and exceeding the reported assay imprecision with a considerable margin. Results: We found considerably stronger reactivity toward animal antibodies, particularly mouse IgG1 and rabbit IgG, in sera from RF-positive RA-patients compared to the control group (Fig. 1a -b). In the Abbott β-hCG assay, interference was shown in 6 out of the 30 tested sera (Fig. 2a ). In the 27-plex cytokine assays, interference was demonstrated in 7 out of 10 tested sera (for 3-14 analytes). Furthermore, 17 out of the 27 cytokine assays were found to be susceptible to interference (Fig. 2b ). Interference was shown in 2 out of 33 samples in the sTfR assay. In unblocked samples, sTfR values were 8.1 and 8.2 mg/L, vs. 4.2 mg/L and 6.0 mg/L in blocked samples, respectively. Additionally, 3 sera had >25% relative difference, but the results were within the reference range. Conclusion: Reactivity to animal antibodies used in immunoassays is common in sera from RF-positive RA patients and are associated with falsely elevated results in commercial immunoassays. In our cohort, interference was demonstrated in a considerable proportion of samples in the Abbott hCG and 27-plex cytokine assays. Physicians as well as researchers, laboratories and assay manufacturers must be alert to the risk of falsely elevated test results in RF positive RA patients, particularly when results are unexpected or discordant with clinical findings. False test results may interfere with research results, and also lead to potentially harmful diagnostic and therapeutic interventions if unrecognised. References: [1] Bolstad N, et al. Heterophilic antibody interference in immunometric assays. Best Pract Res Clin Endocrinol Metab 2013;27(5):647-61. [2] Norli ES, et al. Diagnostic spectrum and 2-year outcome in a cohort of patients with very early arthritis. RMD Open 2017;3(2):e000573. [3] Bolstad N, et al. Heterophilic antibody interference in commercial immunoassays; a screening study using paired native and pre-blocked sera. Clinical Chem Lab Med 2011;49(12):2001-6. Disclosure of Interests: Johanna Elin Gehin Speakers bureau: Roche, Rolf Anton Klaasen: None declared, Ellen Sauar Norli: None declared, Silje Watterdal Syversen Speakers bureau: Roche, Thermo Fisher, Guro Løvik Goll Consultant of: Novartis, Pfizer, Speakers bureau: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, David J Warren: None declared, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Kjell Johannes Nustad: None declared, Maria D Mjaavatten Speakers bureau: Pfizer, Abbott, Nils Bolstad Consultant of: Pfizer, Janssen, Speakers bureau: Orion Pharma, Napp Pharmaceuticals, Takeda, Roche, Novartis